Variations in Degradability Properties of Low Density Polyethylene Blended with Potato Starch - Kumar, Ramkesto; Sharma, Sanjay K. (Asian Journal of Chemistry, 2018)
The conversion of existing synthetic plastics to biodegradable would be one of the efficient path to reduce the solid waste in environment with the reduction of durability and inertness. In the present study, the extent of degradation of low density polyethylene (LDPE) blended with potato starch was evaluated. Samples were processed with different concentrations of potato starch (5, 10, 15, 20 and 25 %). Glycerol as a plasticizer and Fe2(SO4)3 as a pro-oxidant were added to the compound. The effect of potato starch variations on the mechanical properties (tensile strength and elongation), melt flow rate and density of the blended materials were examined. The biodegradation of the compounds in soil was evaluated in terms of loss of mass on regular intervals of 2, 4 and 6 months. Further the outcomes were also verified by FTIR and SEM. The results shown that with higher percentage of potato starch content, the biodegradability of the compounds enhanced. The biodegradation of the samples in soil burial after six months shown that the mass of the compounds decreased with higher percentage of potato starch concentrations.